2011
DOI: 10.1002/ptr.3423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cinnamoyl and Flavonol Glucosides Derived from Cherry Blossom Flowers on the Production of Advanced Glycation End Products (AGEs) and AGE‐induced Fibroblast Apoptosis

Abstract: Cherry blossom flowers are familiar to the Japanese, and some species of the flowers soaked in salty vinegar are used as processed foods. The constituents of aqueous ethanol extract from cherry blossom (Prunus lannesiana) flowers (CBE) were examined and cinnamoyl and flavonol glucosides were isolated. To elucidate the pharmacological functions of CBE and its constituents, their effects on the production of advanced glycation end products (AGEs) and on AGE-induced fibroblast damage were examined. CBE and 1-O-(E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…The IC 50 values (Table 1) of 1 and 2 were 85 and 18 μM, respectively. As shown in Table 1, the IC 50 value of aminoguanidine hydrochloride as a reference compound was 0.9 mM (= 99 μg/ml) in accordance with the reported IC 50 value (138 μg/ml) (Shimoda et al, 2011). Thus, a part of the AGEs formation inhibitory activity of OML-ext is attributable to these two compounds.…”
Section: Samplessupporting
confidence: 83%
See 1 more Smart Citation
“…The IC 50 values (Table 1) of 1 and 2 were 85 and 18 μM, respectively. As shown in Table 1, the IC 50 value of aminoguanidine hydrochloride as a reference compound was 0.9 mM (= 99 μg/ml) in accordance with the reported IC 50 value (138 μg/ml) (Shimoda et al, 2011). Thus, a part of the AGEs formation inhibitory activity of OML-ext is attributable to these two compounds.…”
Section: Samplessupporting
confidence: 83%
“…AGE formation activity was measured according to the method of Shimoda et al (2011) with minor modification. The test sample was dissolved with dimethyl sulfoxide (DMSO) and diluted with sodium phosphate buffer (PBS, 0.2 M KH 2 PO 4 , 0.2 M NaOH, pH 7.2) to a final DMSO concentration of 5% v/v.…”
Section: In Vitro Ages Formation Inhibition Assay By Incubation Of Glmentioning
confidence: 99%
“…Most nutrient absorption occurs in the small intestine, but there is still some nutrient absorption in the colon with the proximal colon being exposed to more luminal nutrients than the distal colon. Querectin in the luminal contents could reduce oxidative damage, decrease formation of advanced glycation end products and chelate iron (68-70). In addition, quercetin has been shown to function as an epigenetic regulator (71).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we assumed that CMA might play an important role in the AGE-breaking activity of peanut extracts. AGE inhibitory activities have been shown to increase in strength with an increasing number of hydroxyl groups on positions 3,4′ hydroxyl group flavonoids [ 48 ]. Moreover, several studies have reported that positions 6 and 8 of the polyphenol A-ring are the major active sites for trapping MGO [ 45 ].…”
Section: Discussionmentioning
confidence: 99%